Upaya Guru dalam Meningkatkan Perhatian dan Dorongan Belajar Akidah Akhlak - Aminah Aminah (Program Pascasarjana UNU Surakarta, 2023)
This study aims to describe the efforts of Akidah Akhlak teachers in increasing the attention and encouragement of learning for Class X MAN 1 Pontianak students in the learning process. A qualitative approach with a case study type is used in this study. Main data collection used in-depth interviews through semi-structured interview guidelines with 5 (five) students of Class X MAN 1 Pontianak. The data analysis technique used is the Miles and Huberman model through 3 (three) stages, (1) data condensation, (2) data presentation, and (3) drawing conclusions. The results of this study found that the efforts that can be made by Akidah Akhlak teachers to increase attention to students, namely (1) adding special study hours for students who need additional study hours, (2) giving advice about the importance of learning Akidah Akhlak, and (3) know the characteristics of students in depth. And map it out. Then, the learning encouragement that Akidah Akhlak teachers can give students is, (1) forming study groups, (2) holding competitions or competitions, and (3) giving project assignments that stimulate students' critical power.